The mediating effect of employee engagement on the relationship between talent management practices and employee retention in the information and technology (IT) organizations in Selangor / Nurul Ezaili Alias - Alias, Nurul Ezaili (2014)
As Information and Technology (IT) industry is vital to the country’s economic growth, it is important to ensure the smoothness operations so that long term growth and development can be achieved with fewer obstacles. Hence, a constant availability o f a large pool of talented and experienced people is crucial to carry out functions. However, employee turnover issue is a critical phenomenon within IT industry globally and locally. To curb this issue, academic attentions have diverted the focus upon the implementation of talent management practices on both employee engagement and employee retention. This study seeks to determine the relationships between talent management practices (managerial support, employee career development and rewards and recognitions), employee engagement and employee retention within IT organizations in Selangor. This is a quantitative study. The research instrument comprises of a self-administered questionnaire. A convenience sampling technique was used for this research. A total of 581 respondents responded valid questionnaires and it gives an average response rate o f 77 % for the study. Data gathered were initially analysed using SPSS version 20.0. The findings of Pearson correlation analysis indicate talent management practices (managerial support, employee career development and rewards and recognitions) have positive correlation with employee engagement. It was also found that employee engagement has positive correlation with employee retention. The results of hierarchical regression analysis on determining the mediating effect o f a mediator (employee engagement) indicate employee engagement mediated the relationship between talent management practice (employee career development and rewards and recognition) and employee retention individually.